Melacak Ideologi di Balik Gemuruh “Heavy Metal” - Fajar Junaedi (Jurnal Komunikasi)
Heavy metal has been an influential and popular music around the world. Its popularity has reached different countries and nations. As a genre of rock music, heavy metal comes from everyday life experience of the musicians. Heavy metal musicians, mostly, are young. So, heavy metal is fully expressed the resistance of youth. Behind its popularity, heavy metal has ideology that can be articulated in different terms, like as a cock rock and androgyny in gender perspective. The resistance of heavy metal has caused moral panic in dominant class.